Environmental behavior of university students - Torroba-Díaz, Macarena; Bajo-Sanjuan, Anna; Callejón-Gil, Ángela; Rosales-Pérez, Ana Maria; López-Marfil, Lidia (Emerald, 2023)
This study aims to build a model for the analysis of the environmental behavior of university students. A partial least square method was adopted, and a questionnaire on intelligence, knowledge, attitude and environmental behavior was performed on 480 Spanish university students. The results indicate that environmental intelligence positively affects university students’ environmental behavior through environmental knowledge and attitude. The conclusions of the present study are based on a sample drawn from Spanish university students. Therefore, new studies are needed to cover other educational institutions and cultural contexts. Many university students’ environmental behavior depends on implementing educational actions that improve their environmental intelligence and knowledge. The study suggests that educational programs should implement strategies that maintain a sense of responsibility toward the sustainable development of university students, ensuring that future generations can live a quality life in a sustainable and safe environment. The present study identifies the mechanism through which the environmental behavior of university students is formed.
Política editorial de acceso abierto: https://v2.sherpa.ac.uk/id/publication/2806?template=romeo
Keywords: Educación ambiental; University students; Partial least square; Environmental behavior; Environmental education; Sustainable development strategy